KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DENGANPENDEKATAN REALISTIC MATHEMATIC EDUCATION - Melania Sparingga (Departemen Matematika, 2018)
The ability of mathematical communicati low ability of students' mathematical communication is caused by the lack of training students in conveying their ideas. Mathematics is also less associated with the reality that students can understand, so students have difficulty in applying mathematical concepts that they learn. One of the learning approaches that relate between mathematical concepts and the real world is Realistic Mathematic Education. The purpose of this study is to determine whether the mathematical communication skills of students with Realistic Mathematic Education approach is better than the mathematical communication ability of students with conventional learning in class VIII SMP Pembangunan Laboratorium UNP. The type of research conducted is quasi experiment (quasi experiment) with the design model Static Group Design. The sample of the study were students of class VIII.A and VIII.B SMP embangunan Laboratorium UNP. The research instrument used is the final test of students' mathematical communication ability. The average value of the experimental class is 68.1 and the control class average is 53.9. The result of analysis by using statistical test, obtained that hypothesis significant. That is, the mathematical communication skills of students who study the approach of RealisticMathematic Education is better than the mathematical communication skills of students who learn with conventionallearning. Keywords–The Ability of Mathematical Communication, Realistic Mathematics Education Approach